Clinical features and risk factors of older adults with bloodstream infection - Mengxi Ding; Yachan Ning; Lipo Song; Xueyuan Yu; Bin Yan; Peijuan Li; Wei Tian; Rongrong Zhang; Wei Chen; Jie Zhen; Fang Lin; Xun Huang; et al. (BMC Geriatrics)
Abstract Objective To investigate the clinical features and risk factors of bloodstream infections in the older adults. Methods This was a prospective cohort multicenter study. According to the inclusion and exclusion criteria, older adults with suspected bloodstream infections from December 2020 to June 2023 were included in the analysis of the clinical features of older adults bloodstream infections. Results A total of 338 older adultswith suspected bloodstream infections were included, of which 141 were diagnosed with bloodstream infections. The proportion of gram-negative bacteria (47.5%) was close to that of gram-positive bacteria (46.1%), while the proportion of gram-negative bacteria was slightly higher.The common clinical manifestations of bloodstream infection were fever (75.2%), decreased level of consciousness (24.8%), chills (14.2%), shock (12.1%), etc.Multivariate regression analysis showed high procalcitonin levels at admission (OR = 2.008, 95%CI 1.258–3.206, P = 0.003) and heart rate > 90 beats/min (OR = 2.104, 95%CI 1.302-3.400). P = 0.002), arterial partial blood pressure of carbon dioxide < 32 mmHg (OR = 1.922, 95%CI 1.025–3.601, P = 0.042), and coronary heart disease (OR = 1.909, 95%CI 1.134–3.213), P = 0.015) were independent risk factors for bloodstream infection in the older adults. Conclusion The proportion of gram-negative and gram-positive bacteria in bloodstream infections in older adults was similar. The common clinical features of bloodstream infection in the older adults are fever and a decreased level of consciousness, and there was no significant difference in systemic clinical manifestations between bloodstream infection and non-bloodstream infection. High procalcitonin (PCT) level, heart rate > 90 beats/min, arterial partial pressure of carbon dioxide (PaCO2) < 32 mmHg, and underlying coronary heart disease were independent risk factors for bloodstream infection in older adults.